An anti-drip type organic-inorganic flame retardant and its preparation method and application

Preparation of hyperbranched droplet-resistant organic-inorganic flame retardant with hyperbranched structures through co-hydrolysis reaction, solving the problem of droplets of polymer materials, improving flame retardancy and fluidity, reducing the amount of flame retardant added, and is suitable for a variety of purposes Polymer materials.

CN118638343BActive Publication Date: 2024-12-24DONGHUA UNIV +3
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411095417.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2024-12-24
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

Existing polymer materials are prone to cause droplets when burning, resulting in severe scalding and secondary ignition. The existing droplet anti-melt technology has high requirements for equipment, affects the crystallinity or mechanical properties of the material, and has a large amount of flame retardant added. , affect industrial application.

Method used

The anti-droplet-resistant organic-inorganic flame retardant is prepared by co-hydrolysis reaction, and the hyperbranched structure is formed by co-hydrolysis reaction of monolayer α-zirconium phosphate, coupling agent-flame retardant and coupling agent-anti-droplet agent. , combined with DOPO derivatives and silane coupling agent, adjust the pH value and reaction conditions, and prepare low crosslinking, hyperbranched anti-droplet organic-inorganic flame retardant.

Benefits of technology

It achieves efficient droplet resistance, optimizes the flame retardant and flowability of the material, reduces the amount of flame retardant added, improves thermal stability and processability, and is suitable for a variety of polymer materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118638343B_ABST
    Figure CN118638343B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer materials, and discloses an anti-melting drop type organic-inorganic flame retardant and its preparation method and application. The particle size of the anti-melting drop type organic-inorganic flame retardant is 2-3 μm, the degree of branching is 30-40%, the initial thermal decomposition temperature is>350°C, and an exothermic peak appears between 380°C and 420°C on the DSC test curve; the preparation method is: a system containing a monolithic layer of α-zirconium phosphate, a coupling agent-flame retardant, and a coupling agent-anti-melting drop agent is subjected to a co-hydrolysis reaction to obtain an anti-melting drop type organic-inorganic flame retardant; the flame retardant is DOPO or a DOPO derivative; the application is: the anti-melting drop type organic-inorganic flame retardant is melt-blended with a polymer slice and then injection molded to obtain a flame-retardant anti-melting drop plastic product. The present invention has improved thermal stability, good compatibility with a polymer matrix, and can meet the requirements of polymer melt processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials and relates to an anti-melting droplet type organic-inorganic flame retardant and a preparation method and application thereof. Background Art

[0002] The application of polymer materials is becoming more and more extensive, and has spread to all aspects of people's production and life. It is one of the indispensable materials in human production activities. However, polymer materials are flammable, which also seriously threatens people's life and property safety. At the same time, polymer materials are usually accompanied by serious molten droplets during combustion. Molten droplets falling on the human body will cause serious burns, and dripping on other flammable materials will cause secondary ignition. These phenomena undoubtedly increase the complexity and danger of polymer fires. Therefore, how to effectively improve the anti-molten droplet performance of polymer materials has become a key issue that needs to be solved in the field of materials science.

[0003] In order to solve the above problems, the prior art generally adopts copolymerization, blending or post-finishing to achieve the purpose of anti-dripping.

[0004] To achieve anti-melting droplet by copolymerization, the flame retardant and anti-melting droplet units are copolymerized and introduced into the molecular chain of the polymer material, such as patent application CN117512802A and patent application CN116813909A. However, this method has high requirements on the reaction equipment, and the current polymerization equipment often cannot meet the reaction conditions. At the same time, the introduction of the flame retardant functional unit will seriously destroy the regularity of the polymer molecular chain, thereby affecting the crystallinity of the polymer material, and further affecting the subsequent molding process.

[0005] The post-finishing method is to soak the fabric or fabric in a dispersion containing a flame retardant, and then graft and cure it by irradiation or the like, such as CN116427173A. The flame retardancy of the flame-retardant fabric or fabric obtained by the post-finishing method is much worse than that of other methods, and the post-finishing method is not suitable for plastic materials.

[0006] The blending method is to melt-process the flame retardant masterbatch and the polymer matrix to obtain different plastic products. The flame retardant and anti-melting droplet performance of the plastic products prepared in this way can be maintained for a long time, and it is easy to process and will not affect the crystallization performance of the polymer material. However, in order to achieve the purpose of flame retardancy and anti-melting droplet in the prior art, the amount of flame retardant added is relatively high. For example, the amount of flame retardant added in CN116693859A and CN116770453A is 5%~10%. The addition of flame retardant often has a significant effect on the mechanical properties of the material, especially at a high addition amount, the mechanical properties of the material will deteriorate sharply, affecting its processability. At the same time, the raw materials used are mostly POSS structures, which are expensive and difficult to industrialize.

[0007] Therefore, it is of great significance to develop an anti-drip organic-inorganic flame retardant and its preparation method and application to solve the above-mentioned problems. Summary of the invention

[0008] The purpose of the present invention is to solve the problems existing in the prior art and to provide an anti-drip type organic-inorganic flame retardant and a preparation method and application thereof.

[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] A method for preparing an anti-melting dripping organic-inorganic flame retardant, wherein a system containing a monolayer of α-zirconium phosphate, a coupling agent-flame retardant, and a coupling agent-anti-melting dripping agent is subjected to a co-hydrolysis reaction to obtain the anti-melting dripping organic-inorganic flame retardant;

[0011] The coupling agent-flame retardant is obtained by reacting the active functional group of the flame retardant with the active functional group of the silane coupling agent A; the flame retardant is DOPO or a DOPO derivative;

[0012] The coupling agent-anti-drip agent is obtained by reacting the active functional group of the anti-drip agent with the active functional group of the silane coupling agent B; the structural formula of the anti-drip agent is as follows:

[0013] or ;

[0014] In the formula, -R- is -CH=CH-, -C≡C-, -CH=N- or -N=N-; at least one of -R1 to -R6 is an active functional group, which is -NH2, -COOH or -SO3H, and the rest are -H;

[0015] During the co-hydrolysis reaction, the hydrolyzable functional group of silane coupling agent A becomes -OH connected to the silicon atom, and the hydrolyzable functional group of silane coupling agent B becomes -OH connected to the silicon atom. Different -OH connected to the silicon atom react with each other and between the -OH connected to the silicon atom and the P-OH on the monolithic α-zirconium phosphate.

[0016] As the preferred technical solution:

[0017] The method for preparing an anti-melting droplet type organic-inorganic flame retardant as described above, wherein the flame retardant is DOPO, and the silane coupling agent A is γ-methacryloxypropyltrimethoxysilane or vinyltrimethoxysilane;

[0018] Alternatively, the flame retardant is a hydroxyl DOPO derivative (e.g., 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (CAS No. 99208-50-1), 1,2-Benzenediol, 4-(6-oxido-6H-dibenz[c,e][1,2]oxaphosphorin-6-yl)- (CAS No. 102416-21-7)) or an amino DOPO derivative (e.g., DOPOBQ-dietherdiamine (CAS No. 947342-47-4), and the silane coupling agent A is γ-glycidyloxypropyltrimethoxysilane or γ-glycidyloxypropyltriethoxysilane;

[0019] Alternatively, the flame retardant is a carboxyl DOPO derivative (such as DDP (CAS No. 63562-33-4)), and the silane coupling agent A is γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane or N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.

[0020] The preparation method of the anti-melting droplet type organic-inorganic flame retardant as described above, the preparation process of the coupling agent-flame retardant is: after adding silane coupling agent A to the flame retardant solution, adjusting the pH value of the system, reacting at 0.1MPa and 25-120°C for 3-12h, and post-treating to obtain the coupling agent-flame retardant;

[0021] The concentration of the flame retardant solution is 10-20wt%, and the solvent is methanol, ethanol, toluene, dichloromethane, chloroform, acetone, dimethyl sulfoxide or DMF;

[0022] The molar ratio of the flame retardant to the silane coupling agent A is 1:1-3;

[0023] When the flame retardant is DOPO, the pH value of the system is adjusted to 7~8; when the flame retardant is a hydroxyl DOPO derivative or an amino DOPO derivative, the pH value of the system is adjusted to 8~12; when the flame retardant is a carboxyl DOPO derivative, the pH value of the system is adjusted to 4~6.

[0024] In the preparation method of the anti-drip type organic-inorganic flame retardant as described above, the silane coupling agent B is γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane or N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane.

[0025] The preparation method of the anti-drip type organic-inorganic flame retardant as described above, the preparation process of the coupling agent-anti-drip agent is: after adding the silane coupling agent B and the catalyst to the anti-drip agent solution, reacting at 0.1-0.3MPa and 25-120°C for 3-12h, and post-treating to obtain the coupling agent-anti-drip agent;

[0026] The concentration of the anti-drip agent solution is 10-20wt%, and the solvent is toluene, dichloromethane, chloroform, acetone, dimethyl sulfoxide or DMF;

[0027] The molar ratio of the anti-drip agent to the silane coupling agent B is 1:1~2;

[0028] The catalyst is azobisisobutyronitrile, 1,3-dicyclohexylcarbodiimide or p-toluenesulfonic acid;

[0029] The mass of the catalyst is 0.05~0.2% of the mass of the anti-dripping agent.

[0030] The preparation method of the above-mentioned anti-melting droplet type organic-inorganic flame retardant comprises the following specific steps:

[0031] (1) using a stripping agent to strip the layered α-zirconium phosphate in a solvent to obtain a paste consisting of a single layer of α-zirconium phosphate and a solvent;

[0032] The water content of the paste is 10~15wt%;

[0033] (2) After mixing the coupling agent-flame retardant, the coupling agent-anti-dripping agent, and the paste to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system;

[0034] The mass ratio of coupling agent-flame retardant, coupling agent-anti-drip agent and paste is 1:1:2.5-3. The monolayer α-zirconium phosphate is slightly more than the sum of the coupling agent-flame retardant and coupling agent-anti-drip agent components to prevent the formation of large cross-linked particles during the hydrolysis process.

[0035] In the mixed solvent of ketone and alcohol, the volume ratio of ketone to alcohol is 4-7:1, the ketone is acetone or methyl ethyl ketone, and the alcohol is methanol or ethanol;

[0036] The mass of the mixed solvent of ketone and alcohol is 2.8 to 3.2 times the mass of the mixture, and this ratio is conducive to forming a low cross-linking system during the hydrolysis process;

[0037] (3) Place the mixed reaction system in an ice water bath and stir for 30 to 60 minutes, then drop a NaOH solution into the system, heat the system to 60 to 70°C and react for 20 to 24 hours, and then post-treat the system to obtain an anti-melting organic-inorganic flame retardant;

[0038] The concentration of NaOH solution is 0.1~1mol / L, and the solvent is water;

[0039] The mass of the NaOH solution is 0.1 to 0.12 times the mass of the mixed solvent of ketone and alcohol, which can ensure the hydrolysis efficiency and facilitate the formation of a low cross-linking system;

[0040] The drop acceleration rate is 3~4s / drop, which can control the hydrolysis reaction process to form a low cross-linking system and prevent the formation of large particles due to excessive hydrolysis and cross-linking, which affects its application in the polymer matrix.

[0041] The method for preparing the above-mentioned anti-melting droplet type organic-inorganic flame retardant, step (1) is specifically as follows:

[0042] (1.1) Add the stripping agent solution dropwise into the layered α-zirconium phosphate dispersion at a dropping speed of 1 to 2 seconds per drop, accompanied by mechanical stirring and ultrasound, and continue to react until the pH value reaches 7 to 8 after the dropping is completed;

[0043] The stripping agent is one or more of D-aminopropanol, 4-amino-1-butanol, 2-aminocyclohexanol, 6-amino-1-hexanol, 3-aminobutanol, 3-amino-1,2-propylene glycol, tromethamine, tetrabutylammonium hydroxide, and hexadecyltrimethylammonium hydroxide;

[0044] The concentration of the stripping agent solution is 10wt%, and the solvent is deionized water;

[0045] The average particle size of the layered α-zirconium phosphate is 2 μm;

[0046] The concentration of the layered α-zirconium phosphate dispersion is 10-15 wt % to prevent gelation during the stripping and modification process, and the solvent is deionized water;

[0047] The mass ratio of layered α-zirconium phosphate to stripping agent is 1:0.6~0.8;

[0048] (1.2) Use an acid solution to adjust the pH value of the reaction system to 2-3 to ensure that the stripping agent is completely free in the solvent, centrifuge (speed of 6000-10000 r / min), remove the upper layer of liquid, and obtain a translucent paste-like liquid;

[0049] The acid solution is a hydrochloric acid aqueous solution, a nitric acid aqueous solution or a phosphoric acid aqueous solution;

[0050] (1.3) After adding deionized water to the translucent paste-like liquid, stir, centrifuge, remove the upper liquid, repeat the above operation 3 times, and then perform rotary evaporation to obtain a paste.

[0051] The present invention also provides an anti-melting dripping type organic-inorganic flame retardant prepared by the preparation method of an anti-melting dripping type organic-inorganic flame retardant as described in any of the preceding items, wherein the particle size of the anti-melting dripping type organic-inorganic flame retardant is 2-3 μm (from which it can be seen that it has a "low cross-linking" structural feature), the degree of branching is 30-40% (from which it can be seen that it has a "hyperbranching" structural feature), the initial thermal decomposition temperature is >350°C, and an exothermic peak appears between 380°C and 420°C on the DSC test curve (indicating that the unsaturated conjugated cross-linkable molecules containing benzene rings undergo a cross-linking reaction).

[0052] The present invention also provides the use of the above-mentioned anti-drip organic-inorganic flame retardant, and the anti-drip organic-inorganic flame retardant is melt-blended with polymer chips and then injection-molded to obtain a flame-retardant anti-drip plastic product.

[0053] As the preferred technical solution:

[0054] For the above-mentioned application, the content of the anti-drip type organic-inorganic flame retardant in the flame retardant anti-drip plastic product is 3-5wt%;

[0055] The polymer chips are polyester chips, and the melt index of the flame retardant and anti-melting drip plastic products at 275°C and 2.16kg is 120~150g / 10min (from this it can be seen that the flame retardant and anti-melting drip plastic products have excellent fluidity), LOI is 33~35% (from this it can be seen that the flame retardant and anti-melting drip plastic products have excellent flame retardancy), UL-94 reaches V0 grade (from this it can be seen that the flame retardant and anti-melting drip plastic products have excellent anti-melting properties), and the complex viscosity at 370°C is 208~273Pa·s.

[0056] Principle of the invention:

[0057] The present invention utilizes different functional group types on the coupling agent to connect the flame retardant and the anti-melting dripping agent to the coupling agent through chemical reaction, respectively, to obtain the coupling agent-flame retardant and the coupling agent-anti-melting dripping agent, and then the system containing the monolithic α-zirconium phosphate, the coupling agent-flame retardant and the coupling agent-anti-melting dripping agent is subjected to co-hydrolysis reaction. During the co-hydrolysis reaction, the hydrolyzable functional group of the silane coupling agent A becomes -OH connected to the silicon atom, and the hydrolyzable functional group of the silane coupling agent B becomes -OH connected to the silicon atom. Different -OHs connected to the silicon atom and -OHs connected to the silicon atom react with each other with P-OH on the monolithic α-zirconium phosphate. In this way, the flame retardant and the anti-melting dripping agent can be connected to the monolithic α-zirconium phosphate at the same time, and the flame retardant and the anti-melting dripping agent react to form a hyperbranched structure, so that the anti-melting dripping type organic-inorganic flame retardant has the structural characteristics of "hyperbranching".

[0058] Flame retardants and anti-drip agents can make flame retardant and anti-drip plastic products have excellent flame retardancy and anti-drip properties, because when flame retardant and anti-drip plastic products burn, the monolayer α-zirconium phosphate can improve the flame retardancy through the synergistic flame retardant effect of the DOPO group in the flame retardant through the condensed phase and gas phase, and the unsaturated conjugated group containing benzene rings in the anti-drip agent will undergo a cross-linking reaction under the combustion state, so that a larger cross-linking network is formed between particles, thereby greatly increasing the viscosity of the melt and achieving the purpose of anti-drip. The anti-drip agent, flame retardant, and monolayer α-zirconium phosphate can cooperate to form a dense and stable carbon layer, which not only further improves the anti-drip property of the material, but also has the effect of smoke suppression;

[0059] The "hyperbranched" structural feature allows the flame-retardant and anti-drip plastic products obtained by melt-blending the anti-drip organic-inorganic flame retardant with polymer chips and then injection molding to have excellent fluidity; at the same time, the anti-drip organic-inorganic flame retardant has more reactive groups on its surface, which can fully undergo self-crosslinking reaction under high temperature / combustion conditions after being blended into the polymer material, thereby achieving the purpose of anti-drip.

[0060] In addition, the present invention can also adjust the reaction conditions so that the anti-drip type organic-inorganic flame retardant has a "low cross-linking" structural feature. The "low cross-linking" structural feature enables it to maintain a micron-level size structure. When it is added to a polymer, it will not affect the processability of the polymer and can be well dispersed.

[0061] The flame retardant and anti-drip agent of the present invention are both small molecules. If they are directly blended with a polymer matrix together with a monolithic α-zirconium phosphate, they cannot meet the requirements of melt processing, have poor processability, and have poor thermal stability and are easy to migrate in the polymer matrix, which causes many problems during application. The present invention grafts both the flame retardant and the anti-drip agent onto the surface of a monolithic α-zirconium phosphate to form an organic-inorganic hybrid system, which has improved thermal stability and good compatibility with the polymer matrix, and can meet the requirements of polymer melt processing.

[0062] Beneficial effects:

[0063] The anti-melting dripping organic-inorganic flame retardant of the present invention has a monolayer α-zirconium phosphate and a silicon-oxygen cross-linking system as a skeleton, has a low cross-linking structure, forms micron-sized particles, and has improved thermal stability after organic-inorganic hybridization, and has good compatibility with the polymer matrix, can be well dispersed in the polymer matrix, meets the requirements of polymer processing, and does not affect the processability. The organic-inorganic hybrid nanoparticles also have a hyperbranched structure, and a large number of functional groups on the surface are conducive to their flame retardant and anti-melting dripping effects under combustion. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1It is a schematic structural diagram of the anti-drip type organic-inorganic flame retardant of the present invention;

[0065] Figure 2 This is a graph showing how the complex viscosity of the polyester chips and the flame-retardant and anti-drip plastic products in Example 1 of the present invention changes with temperature. DETAILED DESCRIPTION

[0066] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0067] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0068] Degree of branching: High-resolution solid-state nuclear magnetic resonance is used to measure the flame retardant and anti-drip plastic products.

[0069] Initial thermal decomposition temperature: The anti-melting droplet type organic-inorganic flame retardant is measured using a thermogravimetric analyzer. The heating rate during the test is 10°C / min, the test temperature range is 30~700°C, and the temperature at which the thermal weight loss is 5wt% is the initial thermal decomposition temperature.

[0070] DSC test: Differential scanning calorimeter is used to measure the anti-melting droplet type organic-inorganic flame retardant. The heating rate during the test is 10℃ / min and the test temperature range is 30~600℃.

[0071] Melt index at 275°C and 2.16kg: The flame retardant and anti-drip plastic products are measured using a melt index meter.

[0072] LOI: Flame retardant and drip-resistant plastic products are tested in accordance with GB / T 2406.2-2009. An oxygen index tester is used for the test, and the top surface ignition method A is used to ignite the sample.

[0073] UL-94: The flame retardant and dripping-resistant plastic products are tested in accordance with the test method B-vertical burning test in the GB / T 2408-2008 standard, and a vertical burning tester is used for the test.

[0074] Complex viscosity: The flame retardant and anti-drip plastic products are measured using a rotational rheometer; the mode is a variable temperature mode, and the test temperature range is 300~400℃.

[0075] Example 1

[0076] A method for preparing an anti-drip type organic-inorganic flame retardant, the specific steps are as follows:

[0077] (1) Preparation of raw materials;

[0078] Flame retardant solution: solute is DOPO, solvent is methanol, concentration is 10wt%;

[0079] Silane coupling agent A: γ-methacryloxypropyltrimethoxysilane;

[0080] Anti-drip agent solution: The structural formula of the solute is , the solvent is dimethyl sulfoxide, and the concentration is 10wt%;

[0081] Silane coupling agent B: γ-aminopropyltriethoxysilane;

[0082] Catalyst: azobisisobutyronitrile;

[0083] Stripping agent solution: the solute is a mixture of D-aminopropanol and 2-aminocyclohexanol in a mass ratio of 1:1, the solvent is deionized water, and the concentration is 10wt%;

[0084] Layered α-zirconium phosphate dispersion: The manufacturer of layered α-zirconium phosphate is Shanghai Runhe Nanomaterial Technology Co., Ltd., the brand is RHA-ZR, the average particle size is 2 μm, the dispersion medium is deionized water, and the concentration is 10wt%;

[0085] Acid solution: hydrochloric acid aqueous solution, concentration is 1 mol / L;

[0086] Deionized water;

[0087] A mixed solvent of ketone and alcohol: the ketone is acetone, the alcohol is methanol, and the volume ratio of ketone to alcohol is 4:1;

[0088] NaOH solution: concentration is 0.1 mol / L, the solvent is water;

[0089] (2) Preparation of coupling agent-flame retardant;

[0090] After adding silane coupling agent A dropwise to the flame retardant solution, the pH value of the system was adjusted to 7, and the mixture was reacted at 0.1 MPa and 65° C. for 8 h. After post-treatment, a coupling agent-flame retardant was obtained; wherein the molar ratio of the flame retardant to the silane coupling agent A was 1:1;

[0091] (3) Preparation of coupling agent-anti-drip agent;

[0092] After adding silane coupling agent B and catalyst to the anti-drip agent solution, reacting at 0.1 MPa and 25° C. for 3 hours, and post-treating to obtain coupling agent-anti-drip agent; wherein the molar ratio of the anti-drip agent to the silane coupling agent B is 1:1.5, and the mass of the catalyst is 0.05% of the mass of the anti-drip agent;

[0093] (4) Preparation of anti-drip type organic-inorganic flame retardant;

[0094] (4.1) adding the stripping agent solution to the layered α-zirconium phosphate dispersion at a rate of 1 second / drop, accompanied by mechanical stirring and ultrasound during the addition, and continuing to react until the pH value is 7 after the addition is completed; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.6;

[0095] (4.2) Adjust the pH value of the reaction system to 2 with an acid solution, centrifuge (speed 6000r / min), remove the upper liquid, and obtain a translucent paste-like liquid;

[0096] (4.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 15 wt%;

[0097] (4.4) After mixing a coupling agent-flame retardant, a coupling agent-anti-melting agent, and a paste in a mass ratio of 1:1:3 to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system; wherein the mass of the mixed solvent of ketone and alcohol is 2.8 times the mass of the mixture;

[0098] (4.5) The mixed reaction system was placed in an ice-water bath and stirred for 60 min, and then NaOH solution was added dropwise at a rate of 3 s / drop. After the addition was completed, the temperature was raised to 68°C and the mixture was reacted for 20 h. After post-treatment, an anti-melting organic-inorganic flame retardant was obtained; wherein the mass of the NaOH solution was 0.12 times the mass of the mixed solvent of ketone and alcohol.

[0099] The resulting anti-drip organic-inorganic flame retardant (whose structure is as follows Figure 1 The particle size of the polyol (as shown) is 2~3μm, the degree of branching is 32%, the initial thermal decomposition temperature is 365℃, and an exothermic peak appears at 382℃ on the DSC test curve.

[0100] An application of an anti-drip type organic-inorganic flame retardant, the anti-drip type organic-inorganic flame retardant prepared in this embodiment is melt-blended with polyester chips (manufacturer is China Petrochemical Corporation, brand FG600) and then injection molded to form a flame-retardant anti-drip plastic product; wherein, the process parameters of melt blending are: screw zone 1 temperature 240°C, zone 2 temperature 260°C, zone 3 temperature 270°C, zone 4 temperature 275°C, zone 5 temperature 270°C, zone 6 temperature 260°C, zone 7 temperature 260°C; injection molding process parameters are: nozzle temperature 260°C, stage 1 temperature 265°C, stage 2 temperature 270°C, stage 3 temperature 265°C.

[0101] The content of the anti-drip type organic-inorganic flame retardant in the flame retardant and anti-drip plastic product finally obtained is 3wt%; Figure 2As shown, the complex viscosity of the flame retardant and anti-melting drip plastic product at 370°C is 208Pa·s. It can also be seen from the figure that, compared with polyester chips, the flame retardant and anti-melting drip plastic product has a lower complex viscosity at processing temperature (before 310°C), indicating that its processing performance is better, while at high temperature or combustion temperature (above 350°C), it has a higher complex viscosity and lower fluidity, so it has better anti-melting drip performance; the melt index of the flame retardant and anti-melting drip plastic product at 275°C and 2.16kg is 120g / 10min, the LOI is 33.2%, and the UL-94 reaches V0 grade.

[0102] Comparative Example 1

[0103] A method for preparing an anti-melting dripping type organic-inorganic flame retardant is basically the same as that in Example 1, except that: step (2) is omitted, coupling agent-flame retardant is not added in step (4.4), and step (4.5) is: placing the mixed reaction system in an ice-water bath and stirring for 60 minutes, then dropping a NaOH solution therein at a rate of 3 seconds / drop, heating the mixture to 68°C after the dropping is complete, reacting for 20 hours, performing post-treatment, and mixing the post-treatment product with a flame retardant (the type and addition amount are the same as those in Example 1) to obtain an anti-melting dripping type organic-inorganic flame retardant; wherein the mass of the NaOH solution is 0.12 times the mass of the mixed solvent of ketone and alcohol.

[0104] The initial thermal decomposition temperature of the finally obtained anti-drip organic-inorganic flame retardant is 285°C, and an exothermic peak appears at 364°C on the DSC test curve.

[0105] The application of an anti-drip type organic-inorganic flame retardant is basically the same as Example 1, except that the anti-drip type organic-inorganic flame retardant is the anti-drip type organic-inorganic flame retardant prepared in this comparative example.

[0106] The final flame retardant and anti-drip plastic product has a complex viscosity of 86 Pa·s at 370°C, a melt index of 123 g / 10 min at 275°C and 2.16 kg, an LOI of 28.3%, and a UL-94 V-1 grade.

[0107] Comparative Example 2

[0108] A method for preparing an anti-melting dripping type organic-inorganic flame retardant is basically the same as that in Example 1, except that: step (3) is omitted, coupling agent-anti-melting dripping agent is not added in step (4.4), and step (4.5) is: placing the mixed reaction system in an ice-water bath and stirring for 60 minutes, then dropping a NaOH solution therein at a rate of 3 seconds / drop, heating the mixture to 68°C after the dropwise addition is completed, reacting for 20 hours, performing post-treatment, mixing the post-treatment product with an anti-melting dripping agent (the type and addition amount are the same as those in Example 1), and obtaining an anti-melting dripping type organic-inorganic flame retardant; wherein the mass of the NaOH solution is 0.12 times the mass of the mixed solvent of ketone and alcohol.

[0109] The initial thermal decomposition temperature of the finally obtained anti-drip organic-inorganic flame retardant is 273°C, and no exothermic peak appears on the DSC test curve.

[0110] The application of an anti-drip type organic-inorganic flame retardant is basically the same as Example 1, except that the anti-drip type organic-inorganic flame retardant is the anti-drip type organic-inorganic flame retardant prepared in this comparative example.

[0111] The final flame retardant and anti-drip plastic product has a complex viscosity of 49 Pa·s at 370°C, a melt index of 135 g / 10 min at 275°C and 2.16 kg, a LOI of 29.5%, and a UL-94 V-2 grade.

[0112] By comparing Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that simultaneously grafting the flame retardant and the anti-drip agent onto the surface of a monolithic α-zirconium phosphate can achieve better flame retardant and anti-drip effects than grafting one of the substances onto the surface of a monolithic α-zirconium phosphate and blending the other substance therewith. This is because the thermal stability of both the flame retardant and the anti-drip agent blended together is relatively poor, resulting in a large amount of decomposition of the flame retardant before the anti-drip agent undergoes cross-linking reaction and the anti-drip agent cannot exhibit its anti-drip effect at high temperature, and the flame retardant and the anti-drip agent cannot fully exert their synergistic effect.

[0113] Example 2

[0114] A method for preparing an anti-drip type organic-inorganic flame retardant, the specific steps are as follows:

[0115] (1) Preparation of raw materials;

[0116] Flame retardant solution: solute is DOPO, solvent is ethanol, concentration is 20wt%;

[0117] Silane coupling agent A: vinyltrimethoxysilane;

[0118] Anti-drip agent solution: The structural formula of the solute is , the solvent is dimethyl sulfoxide, and the concentration is 10wt%;

[0119] Silane coupling agent B: γ-aminopropyltriethoxysilane;

[0120] Catalyst: 1,3-dicyclohexylcarbodiimide;

[0121] Stripping agent solution: the solute is 4-amino-1-butanol, the solvent is deionized water, and the concentration is 10wt%;

[0122] Layered α-zirconium phosphate dispersion: The manufacturer of layered α-zirconium phosphate is Shanghai Runhe Nanomaterial Technology Co., Ltd., the brand is RHA-ZR, the average particle size is 2 μm, the dispersion medium is deionized water, and the concentration is 10wt%;

[0123] Acid solution: hydrochloric acid aqueous solution, concentration is 1 mol / L;

[0124] Deionized water;

[0125] A mixed solvent of ketone and alcohol: the ketone is acetone, the alcohol is methanol, and the volume ratio of ketone to alcohol is 5:1;

[0126] NaOH solution: concentration is 0.3 mol / L, solvent is water;

[0127] (2) Preparation of coupling agent-flame retardant;

[0128] After adding silane coupling agent A dropwise to the flame retardant solution, the pH value of the system was adjusted to 8, and the mixture was reacted at 0.1 MPa and 80° C. for 8 h. After post-treatment, a coupling agent-flame retardant was obtained; wherein the molar ratio of the flame retardant to the silane coupling agent A was 1:1.5;

[0129] (3) Preparation of coupling agent-anti-drip agent;

[0130] After adding silane coupling agent B and catalyst to the anti-drip agent solution, reacting at 0.3 MPa and 120° C. for 8 hours, and post-treating to obtain coupling agent-anti-drip agent; wherein the molar ratio of the anti-drip agent to the silane coupling agent B is 1:2, and the mass of the catalyst is 0.2% of the mass of the anti-drip agent;

[0131] (4) Preparation of anti-drip type organic-inorganic flame retardant;

[0132] (4.1) adding the stripping agent solution to the layered α-zirconium phosphate dispersion at a rate of 1 second / drop, accompanied by mechanical stirring and ultrasound during the addition, and continuing to react until the pH value is 7 after the addition is completed; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.65;

[0133] (4.2) Adjust the pH value of the reaction system to 2 with an acid solution, centrifuge (speed 7000r / min), remove the upper liquid, and obtain a translucent paste-like liquid;

[0134] (4.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper layer of liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 13.4 wt%;

[0135] (4.4) After mixing a coupling agent-flame retardant, a coupling agent-anti-melting agent, and a paste in a mass ratio of 1:1:2.8 to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system; wherein the mass of the mixed solvent of ketone and alcohol is 2.8 times the mass of the mixture;

[0136] (4.5) The mixed reaction system was placed in an ice-water bath and stirred for 45 min, and then NaOH solution was added dropwise at a rate of 3 s / drop. After the addition was completed, the temperature was raised to 60°C and the mixture was reacted for 20 h. After post-treatment, an anti-melting organic-inorganic flame retardant was obtained; wherein the mass of the NaOH solution was 0.12 times the mass of the mixed solvent of ketone and alcohol.

[0137] The particle size of the final anti-drip organic-inorganic flame retardant is 2-3 μm, the branching degree is 38%, the initial thermal decomposition temperature is 380°C, and an exothermic peak appears at 415°C on the DSC test curve.

[0138] An application of an anti-drip type organic-inorganic flame retardant, the anti-drip type organic-inorganic flame retardant prepared in this embodiment is melt-blended with polyester chips (manufacturer is China Petrochemical Corporation, brand FG600) and then injection molded to form a flame-retardant anti-drip plastic product; wherein, the process parameters of melt blending are: screw zone 1 temperature 240°C, zone 2 temperature 260°C, zone 3 temperature 270°C, zone 4 temperature 275°C, zone 5 temperature 270°C, zone 6 temperature 260°C, zone 7 temperature 260°C; injection molding process parameters are: nozzle temperature 260°C, stage 1 temperature 265°C, stage 2 temperature 270°C, stage 3 temperature 265°C.

[0139] The content of anti-drip type organic-inorganic flame retardant in the final flame retardant and anti-drip plastic product is 3.8wt%; the complex viscosity of the flame retardant and anti-drip plastic product at 370°C is 246Pa·s, the melt index at 275°C and 2.16kg is 132g / 10min, the LOI is 33.6%, and the UL-94 reaches V0 grade.

[0140] Example 3

[0141] A method for preparing an anti-drip type organic-inorganic flame retardant, the specific steps are as follows:

[0142] (1) Preparation of raw materials;

[0143] Flame retardant solution: the solute is 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, the solvent is toluene, and the concentration is 10wt%;

[0144] Silane coupling agent A: γ-glycidyloxypropyltrimethoxysilane;

[0145] Anti-drip agent solution: The structural formula of the solute is , the solvent is acetone, the concentration is 15wt%;

[0146] Silane coupling agent B: γ-aminopropyltriethoxysilane;

[0147] Catalyst: 1,3-dicyclohexylcarbodiimide;

[0148] Stripping agent solution: the solute is 3-aminobutanol, the solvent is deionized water, and the concentration is 10wt%;

[0149] Layered α-zirconium phosphate dispersion: The manufacturer of layered α-zirconium phosphate is Changzhou Konada New Material Technology Co., Ltd., the brand is KND-SG300, the average particle size is 2 μm, the dispersion medium is deionized water, and the concentration is 10wt%;

[0150] Acid solution: nitric acid aqueous solution, concentration is 1 mol / L;

[0151] Deionized water;

[0152] A mixed solvent of ketone and alcohol: the ketone is acetone, the alcohol is ethanol, and the volume ratio of ketone to alcohol is 6:1;

[0153] NaOH solution: concentration is 1 mol / L, solvent is water;

[0154] (2) Preparation of coupling agent-flame retardant;

[0155] After adding silane coupling agent A dropwise to the flame retardant solution, the pH value of the system was adjusted to 8, and the mixture was reacted at 0.1 MPa and 50° C. for 6 h. After post-treatment, a coupling agent-flame retardant was obtained; wherein the molar ratio of the flame retardant to the silane coupling agent A was 1:1.2;

[0156] (3) Preparation of coupling agent-anti-drip agent;

[0157] After adding silane coupling agent B and catalyst to the anti-drip agent solution, reacting at 0.15 MPa and 80° C. for 6 hours, and post-treating to obtain coupling agent-anti-drip agent; wherein the molar ratio of the anti-drip agent to the silane coupling agent B is 1:1, and the mass of the catalyst is 0.2% of the mass of the anti-drip agent;

[0158] (4) Preparation of anti-drip type organic-inorganic flame retardant;

[0159] (4.1) adding the stripping agent solution to the layered α-zirconium phosphate dispersion at a rate of 1 second / drop, accompanied by mechanical stirring and ultrasound during the dropping, and continuing to react until the pH value is 7 after the dropping is completed; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.75;

[0160] (4.2) Adjust the pH value of the reaction system to 2 with an acid solution, centrifuge (speed 8000r / min), remove the upper liquid, and obtain a translucent paste-like liquid;

[0161] (4.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 12.8 wt%;

[0162] (4.4) After mixing a coupling agent-flame retardant, a coupling agent-anti-melting agent, and a paste in a mass ratio of 1:1:2.7 to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system; wherein the mass of the mixed solvent of ketone and alcohol is 3 times the mass of the mixture;

[0163] (4.5) The mixed reaction system was placed in an ice-water bath and stirred for 50 min, and then NaOH solution was added dropwise at a rate of 3 s / drop. After the addition was completed, the temperature was raised to 70°C and the mixture was reacted for 21 h. After post-treatment, an anti-melting organic-inorganic flame retardant was obtained; wherein the mass of the NaOH solution was 0.11 times the mass of the mixed solvent of ketone and alcohol.

[0164] The particle size of the final anti-melting droplet type organic-inorganic flame retardant is 2-3 μm, the branching degree is 33%, the initial thermal decomposition temperature is 360°C, and an exothermic peak appears at 396°C on the DSC test curve.

[0165] An application of an anti-drip type organic-inorganic flame retardant, the anti-drip type organic-inorganic flame retardant prepared in this embodiment is melt-blended with polyester chips (manufacturer is China Petrochemical Corporation, brand FG600) and then injection molded to form a flame-retardant anti-drip plastic product; wherein, the process parameters of melt blending are: screw zone 1 temperature 240°C, zone 2 temperature 260°C, zone 3 temperature 270°C, zone 4 temperature 275°C, zone 5 temperature 270°C, zone 6 temperature 260°C, zone 7 temperature 260°C; injection molding process parameters are: nozzle temperature 260°C, stage 1 temperature 265°C, stage 2 temperature 270°C, stage 3 temperature 265°C.

[0166] The content of anti-drip type organic-inorganic flame retardant in the final flame retardant and anti-drip plastic product is 3.5wt%; the complex viscosity of the flame retardant and anti-drip plastic product at 370°C is 224Pa·s, the melt index at 275°C and 2.16kg is 122g / 10min, the LOI is 33.8%, and the UL-94 reaches V0 grade.

[0167] Example 4

[0168] A method for preparing an anti-drip type organic-inorganic flame retardant, the specific steps are as follows:

[0169] (1) Preparation of raw materials;

[0170] Flame retardant solution: the solute is 1,2-Benzenediol,4-(6-oxido-6H-dibenz[c,e][1,2]oxaphosphorin-6-yl)-, the solvent is dichloromethane, and the concentration is 10wt%;

[0171] Silane coupling agent A: γ-glycidyloxypropyltriethoxysilane;

[0172] Anti-drip agent solution: The structural formula of the solute is , the solvent is chloroform, and the concentration is 15wt%;

[0173] Silane coupling agent B: γ-aminopropyltrimethoxysilane;

[0174] Catalyst: p-toluenesulfonic acid;

[0175] Stripping agent solution: the solute is 3-amino-1,2-propylene glycol, the solvent is deionized water, and the concentration is 10wt%;

[0176] Layered α-zirconium phosphate dispersion: The manufacturer of layered α-zirconium phosphate is Shanghai Runhe Nanomaterial Technology Co., Ltd., the brand is RHA-ZR, the average particle size is 2 μm, the dispersion medium is deionized water, and the concentration is 12wt%;

[0177] Acid solution: nitric acid aqueous solution, concentration is 1 mol / L;

[0178] Deionized water;

[0179] A mixed solvent of ketone and alcohol: the ketone is acetone, the alcohol is ethanol, and the volume ratio of ketone to alcohol is 7:1;

[0180] NaOH solution: concentration is 1 mol / L, solvent is water;

[0181] (2) Preparation of coupling agent-flame retardant;

[0182] After adding silane coupling agent A dropwise to the flame retardant solution, the pH value of the system was adjusted to 10, and the mixture was reacted at 0.1 MPa and 25° C. for 3 h. After post-treatment, a coupling agent-flame retardant was obtained; wherein the molar ratio of the flame retardant to the silane coupling agent A was 1:3;

[0183] (3) Preparation of coupling agent-anti-drip agent;

[0184] After adding silane coupling agent B and catalyst to the anti-drip agent solution, reacting at 0.1 MPa and 50° C. for 3 hours, and post-treating to obtain coupling agent-anti-drip agent; wherein the molar ratio of the anti-drip agent to the silane coupling agent B is 1:1, and the mass of the catalyst is 0.05% of the mass of the anti-drip agent;

[0185] (4) Preparation of anti-drip type organic-inorganic flame retardant;

[0186] (4.1) adding the stripping agent solution to the layered α-zirconium phosphate dispersion at a rate of 2 seconds per drop, accompanied by mechanical stirring and ultrasound, and continuing to react until the pH value is 8 after the addition is completed; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.8;

[0187] (4.2) Adjust the pH value of the reaction system to 2 with an acid solution, centrifuge (speed: 9000 r / min), remove the upper layer of liquid, and obtain a translucent paste-like liquid;

[0188] (4.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 11.2 wt%;

[0189] (4.4) After mixing a coupling agent-flame retardant, a coupling agent-anti-melting agent, and a paste in a mass ratio of 1:1:2.6 to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system; wherein the mass of the mixed solvent of ketone and alcohol is 3 times the mass of the mixture;

[0190] (4.5) The mixed reaction system was placed in an ice-water bath and stirred for 30 min, and then NaOH solution was added dropwise at a rate of 3 s / drop. After the addition was completed, the temperature was raised to 63°C and the mixture was reacted for 22 h. After post-treatment, an anti-melting organic-inorganic flame retardant was obtained; wherein the mass of the NaOH solution was 0.1 times the mass of the mixed solvent of ketone and alcohol.

[0191] The particle size of the final anti-drip organic-inorganic flame retardant is 2-3 μm, the branching degree is 40%, the initial thermal decomposition temperature is 368°C, and an exothermic peak appears at 390°C on the DSC test curve.

[0192] An application of an anti-drip type organic-inorganic flame retardant, the anti-drip type organic-inorganic flame retardant prepared in this embodiment is melt-blended with polyester chips (manufacturer is China Petrochemical Corporation, brand FG600) and then injection molded to form a flame-retardant anti-drip plastic product; wherein, the process parameters of melt blending are: screw zone 1 temperature 240°C, zone 2 temperature 260°C, zone 3 temperature 270°C, zone 4 temperature 275°C, zone 5 temperature 270°C, zone 6 temperature 260°C, zone 7 temperature 260°C; injection molding process parameters are: nozzle temperature 260°C, stage 1 temperature 265°C, stage 2 temperature 270°C, stage 3 temperature 265°C.

[0193] The content of anti-drip type organic-inorganic flame retardant in the final flame retardant and anti-drip plastic product is 4.2wt%; the complex viscosity of the flame retardant and anti-drip plastic product at 370°C is 265Pa·s, the melt index at 275°C and 2.16kg is 143g / 10min, the LOI is 34.4%, and the UL-94 reaches V0 grade.

[0194] Example 5

[0195] A method for preparing an anti-drip type organic-inorganic flame retardant, the specific steps are as follows:

[0196] (1) Preparation of raw materials;

[0197] Flame retardant solution: the solute is DOPOBQ-dietherdiamine, the solvent is chloroform, and the concentration is 10wt%;

[0198] Silane coupling agent A: γ-glycidyloxypropyltriethoxysilane;

[0199] Anti-drip agent solution: The structural formula of the solute is , the solvent is DMF, the concentration is 20wt%;

[0200] Silane coupling agent B: γ-aminopropyltrimethoxysilane;

[0201] Catalyst: 1,3-dicyclohexylcarbodiimide;

[0202] Stripping agent solution: the solute is tromethamine, the solvent is deionized water, and the concentration is 10wt%;

[0203] Layered α-zirconium phosphate dispersion: The manufacturer of layered α-zirconium phosphate is Fujian Ruisen New Materials Co., Ltd., the brand is RS-LSG-C, the average particle size is 2μm, the dispersion medium is deionized water, and the concentration is 12wt%;

[0204] Acid solution: phosphoric acid aqueous solution, concentration is 1 mol / L;

[0205] Deionized water;

[0206] A mixed solvent of ketone and alcohol: the ketone is methyl ethyl ketone, the alcohol is ethanol, and the volume ratio of ketone to alcohol is 4.5:1;

[0207] NaOH solution: concentration is 0.5 mol / L, the solvent is water;

[0208] (2) Preparation of coupling agent-flame retardant;

[0209] After adding silane coupling agent A dropwise to the flame retardant solution, the pH value of the system was adjusted to 12, and the mixture was reacted at 0.1 MPa and 50° C. for 3 h. After post-treatment, a coupling agent-flame retardant was obtained; wherein the molar ratio of the flame retardant to the silane coupling agent A was 1:2;

[0210] (3) Preparation of coupling agent-anti-drip agent;

[0211] After adding silane coupling agent B and catalyst to the anti-drip agent solution, reacting at 0.2MPa and 100°C for 10h, and post-treating to obtain coupling agent-anti-drip agent; wherein the molar ratio of the anti-drip agent to the silane coupling agent B is 1:1.8, and the mass of the catalyst is 0.18% of the mass of the anti-drip agent;

[0212] (4) Preparation of anti-drip type organic-inorganic flame retardant;

[0213] (4.1) adding the stripping agent solution to the layered α-zirconium phosphate dispersion at a rate of 2 seconds per drop, accompanied by mechanical stirring and ultrasound during the addition, and continuing to react until the pH value is 8 after the addition is completed; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.6;

[0214] (4.2) Adjust the pH value of the reaction system to 3 with an acid solution, centrifuge (speed of 10000r / min), remove the upper liquid, and obtain a translucent paste-like liquid;

[0215] (4.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 10 wt%;

[0216] (4.4) After mixing a coupling agent-flame retardant, a coupling agent-anti-drip agent, and a paste in a mass ratio of 1:1:2.5 to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system; wherein the mass of the mixed solvent of ketone and alcohol is 3.2 times the mass of the mixture;

[0217] (4.5) The mixed reaction system was placed in an ice-water bath and stirred for 60 min, and then NaOH solution was added dropwise at a rate of 4 s / drop. After the addition was completed, the temperature was raised to 70°C and the mixture was reacted for 23 h. After post-treatment, an anti-melting organic-inorganic flame retardant was obtained; wherein the mass of the NaOH solution was 0.12 times the mass of the mixed solvent of ketone and alcohol.

[0218] The particle size of the final anti-drip organic-inorganic flame retardant is 2-3 μm, the branching degree is 30%, the initial thermal decomposition temperature is 370°C, and an exothermic peak appears at 406°C on the DSC test curve.

[0219] An application of an anti-drip organic-inorganic flame retardant, the anti-drip organic-inorganic flame retardant prepared in this embodiment is melt-blended with polyester chips (manufacturer is China Petrochemical Corporation, brand FG720) and then injection molded to form a flame-retardant anti-drip plastic product; wherein the process parameters of melt blending are: screw zone 1 temperature 240°C, zone 2 temperature 260°C, zone 3 temperature 270°C, zone 4 temperature 275°C, zone 5 temperature 270°C, zone 6 temperature 260°C, zone 7 temperature 260°C; injection molding process parameters are: nozzle temperature 260°C, stage 1 temperature 265°C, stage 2 temperature 270°C, stage 3 temperature 265°C.

[0220] The content of anti-drip type organic-inorganic flame retardant in the final flame retardant and anti-drip plastic product is 5wt%; the complex viscosity of the flame retardant and anti-drip plastic product at 370°C is 273Pa·s, the melt index at 275°C and 2.16kg is 150g / 10min, the LOI is 34.9%, and the UL-94 reaches V0 grade.

[0221] Example 6

[0222] A method for preparing an anti-drip type organic-inorganic flame retardant, the specific steps are as follows:

[0223] (1) Preparation of raw materials;

[0224] Flame retardant solution: solute is DDP, solvent is acetone, concentration is 15wt%;

[0225] Silane coupling agent A: γ-aminopropyltriethoxysilane;

[0226] Anti-drip agent solution: The structural formula of the solute is , the solvent is dichloromethane, the concentration is 20wt%;

[0227] Silane coupling agent B: γ-aminopropyltrimethoxysilane;

[0228] Catalyst: 1,3-dicyclohexylcarbodiimide;

[0229] Stripping agent solution: the solute is tetrabutylammonium hydroxide, the solvent is deionized water, and the concentration is 10wt%;

[0230] Layered α-zirconium phosphate dispersion: The manufacturer of layered α-zirconium phosphate is Fujian Ruisen New Materials Co., Ltd., the brand is RS-LSG-C, the average particle size is 2μm, the dispersion medium is deionized water, and the concentration is 15wt%;

[0231] Acid solution: phosphoric acid aqueous solution, concentration is 1 mol / L;

[0232] Deionized water;

[0233] A mixed solvent of ketone and alcohol: the ketone is methyl ethyl ketone, the alcohol is ethanol, and the volume ratio of ketone to alcohol is 5.5:1;

[0234] NaOH solution: concentration is 0.5 mol / L, the solvent is water;

[0235] (2) Preparation of coupling agent-flame retardant;

[0236] After adding silane coupling agent A dropwise to the flame retardant solution, the pH value of the system was adjusted to 4, and the mixture was reacted at 0.1 MPa and 80° C. for 12 h, and then post-treated to obtain a coupling agent-flame retardant; wherein the molar ratio of the flame retardant to the silane coupling agent A was 1:2.2;

[0237] (3) Preparation of coupling agent-anti-drip agent;

[0238] After adding silane coupling agent B and catalyst to the anti-drip agent solution, reacting at 0.18 MPa and 60° C. for 12 hours, and post-treating to obtain coupling agent-anti-drip agent; wherein the molar ratio of the anti-drip agent to the silane coupling agent B is 1:1.2, and the mass of the catalyst is 0.05% of the mass of the anti-drip agent;

[0239] (4) Preparation of anti-drip type organic-inorganic flame retardant;

[0240] (4.1) adding the stripping agent solution to the layered α-zirconium phosphate dispersion at a rate of 2 seconds per drop, accompanied by mechanical stirring and ultrasound, and continuing to react until the pH value is 8 after the addition is completed; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.7;

[0241] (4.2) Adjust the pH value of the reaction system to 3 with an acid solution, centrifuge (speed: 9000 r / min), remove the upper layer of liquid, and obtain a translucent paste-like liquid;

[0242] (4.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 11.2 wt%;

[0243] (4.4) After mixing a coupling agent-flame retardant, a coupling agent-anti-melting agent, and a paste in a mass ratio of 1:1:2.6 to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system; wherein the mass of the mixed solvent of ketone and alcohol is 3.2 times the mass of the mixture;

[0244] (4.5) The mixed reaction system was placed in an ice-water bath and stirred for 60 min, and then NaOH solution was added dropwise at a rate of 4 s / drop. After the addition was completed, the temperature was raised to 60°C and the mixture was reacted for 24 h. After post-treatment, an anti-melting organic-inorganic flame retardant was obtained; wherein the mass of the NaOH solution was 0.1 times the mass of the mixed solvent of ketone and alcohol.

[0245] The particle size of the final anti-drip organic-inorganic flame retardant is 2-3 μm, the branching degree is 35%, the initial thermal decomposition temperature is 372°C, and an exothermic peak appears at 413°C on the DSC test curve.

[0246] An application of an anti-drip organic-inorganic flame retardant, the anti-drip organic-inorganic flame retardant prepared in this embodiment is melt-blended with polyester chips (manufacturer is China Petrochemical Corporation, brand FG720) and then injection molded to form a flame-retardant anti-drip plastic product; wherein the process parameters of melt blending are: screw zone 1 temperature 240°C, zone 2 temperature 260°C, zone 3 temperature 270°C, zone 4 temperature 275°C, zone 5 temperature 270°C, zone 6 temperature 260°C, zone 7 temperature 260°C; injection molding process parameters are: nozzle temperature 260°C, stage 1 temperature 265°C, stage 2 temperature 270°C, stage 3 temperature 265°C.

[0247] The content of anti-drip type organic-inorganic flame retardant in the final flame retardant and anti-drip plastic product is 3wt%; the complex viscosity of the flame retardant and anti-drip plastic product at 370°C is 214Pa·s, the melt index at 275°C and 2.16kg is 121g / 10min, the LOI is 33.3%, and the UL-94 reaches V0 grade.

[0248] Example 7

[0249] A method for preparing an anti-drip type organic-inorganic flame retardant, the specific steps are as follows:

[0250] (1) Preparation of raw materials;

[0251] Flame retardant solution: solute is DDP, solvent is dimethyl sulfoxide, concentration is 18wt%;

[0252] Silane coupling agent A: γ-aminopropyltrimethoxysilane;

[0253] Anti-drip agent solution: The structural formula of the solute is , the solvent is toluene, and the concentration is 18wt%;

[0254] Silane coupling agent B: N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane;

[0255] Catalyst: 1,3-dicyclohexylcarbodiimide;

[0256] Stripping agent solution: the solute is hexadecyltrimethylammonium hydroxide, the solvent is deionized water, and the concentration is 10wt%;

[0257] Layered α-zirconium phosphate dispersion: The manufacturer of layered α-zirconium phosphate is Changzhou Konada New Material Technology Co., Ltd., the brand is KND-SG300, the average particle size is 2 μm, the dispersion medium is deionized water, and the concentration is 15wt%;

[0258] Acid solution: phosphoric acid aqueous solution, concentration is 1 mol / L;

[0259] Deionized water;

[0260] A mixed solvent of ketone and alcohol: the ketone is methyl ethyl ketone, the alcohol is methanol, and the volume ratio of ketone to alcohol is 6.5:1;

[0261] NaOH solution: concentration is 0.8 mol / L, solvent is water;

[0262] (2) Preparation of coupling agent-flame retardant;

[0263] After adding silane coupling agent A dropwise to the flame retardant solution, the pH value of the system was adjusted to 5, and the mixture was reacted at 0.1 MPa and 120° C. for 6 h, and then post-treated to obtain a coupling agent-flame retardant; wherein the molar ratio of the flame retardant to the silane coupling agent A was 1:2.5;

[0264] (3) Preparation of coupling agent-anti-drip agent;

[0265] After adding silane coupling agent B and catalyst to the anti-drip agent solution, reacting at 0.12MPa and 80°C for 6h, and post-processing, a coupling agent-anti-drip agent is obtained; wherein the molar ratio of the anti-drip agent to the silane coupling agent B is 1:1.1, and the mass of the catalyst is 0.13% of the mass of the anti-drip agent;

[0266] (4) Preparation of anti-drip type organic-inorganic flame retardant;

[0267] (4.1) adding the stripping agent solution to the layered α-zirconium phosphate dispersion at a rate of 2 seconds per drop, accompanied by mechanical stirring and ultrasound, and continuing to react until the pH value is 8 after the addition is completed; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.8;

[0268] (4.2) Adjust the pH value of the reaction system to 3 with an acid solution, centrifuge (speed: 9000 r / min), remove the upper layer of liquid, and obtain a translucent paste-like liquid;

[0269] (4.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 11.2 wt%;

[0270] (4.4) After mixing a coupling agent-flame retardant, a coupling agent-anti-melting agent, and a paste in a mass ratio of 1:1:2.8 to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system; wherein the mass of the mixed solvent of ketone and alcohol is 2.8 times the mass of the mixture;

[0271] (4.5) After the mixed reaction system was placed in an ice-water bath and stirred for 30 min, NaOH solution was added dropwise at a rate of 4 s / drop. After the addition was completed, the temperature was raised to 60°C and the mixture was reacted for 24 h. After post-treatment, an anti-melting organic-inorganic flame retardant was obtained; wherein the mass of the NaOH solution was 0.1 times the mass of the mixed solvent of ketone and alcohol.

[0272] The particle size of the final anti-drip organic-inorganic flame retardant is 2-3 μm, the branching degree is 33%, the initial thermal decomposition temperature is 366°C, and an exothermic peak appears at 398°C on the DSC test curve.

[0273] An application of an anti-drip organic-inorganic flame retardant, the anti-drip organic-inorganic flame retardant prepared in this embodiment is melt-blended with polyester chips (manufacturer is China Petrochemical Corporation, brand FG720) and then injection molded to form a flame-retardant anti-drip plastic product; wherein the process parameters of melt blending are: screw zone 1 temperature 240°C, zone 2 temperature 260°C, zone 3 temperature 270°C, zone 4 temperature 275°C, zone 5 temperature 270°C, zone 6 temperature 260°C, zone 7 temperature 260°C; injection molding process parameters are: nozzle temperature 260°C, stage 1 temperature 265°C, stage 2 temperature 270°C, stage 3 temperature 265°C.

[0274] The content of anti-drip type organic-inorganic flame retardant in the final flame retardant and anti-drip plastic product is 4wt%; the complex viscosity of the flame retardant and anti-drip plastic product at 370°C is 262Pa·s, the melt index at 275°C and 2.16kg is 140g / 10min, the LOI is 34.2%, and the UL-94 reaches V0 grade.

[0275] Example 8

[0276] A method for preparing an anti-drip type organic-inorganic flame retardant, the specific steps are as follows:

[0277] (1) Preparation of raw materials;

[0278] Flame retardant solution: solute is DDP, solvent is DMF, concentration is 20wt%;

[0279] Silane coupling agent A: N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane;

[0280] Anti-drip agent solution: The structural formula of the solute is , the solvent is DMF, the concentration is 10wt%;

[0281] Silane coupling agent B: N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane;

[0282] Catalyst: 1,3-dicyclohexylcarbodiimide;

[0283] Stripping agent solution: the solute is 6-amino-1-hexanol, the solvent is deionized water, and the concentration is 10wt%;

[0284] Layered α-zirconium phosphate dispersion: The manufacturer of layered α-zirconium phosphate is Shanghai Runhe Nanomaterial Technology Co., Ltd., the brand is RHA-ZR, the average particle size is 2 μm, the dispersion medium is deionized water, and the concentration is 10wt%;

[0285] Acid solution: hydrochloric acid aqueous solution, concentration is 1 mol / L;

[0286] Deionized water;

[0287] A mixed solvent of ketone and alcohol: the ketone is methyl ethyl ketone, the alcohol is methanol, and the volume ratio of ketone to alcohol is 4:1;

[0288] NaOH solution: concentration is 1 mol / L, solvent is water;

[0289] (2) Preparation of coupling agent-flame retardant;

[0290] After adding silane coupling agent A dropwise to the flame retardant solution, the pH value of the system was adjusted to 6, and the reaction was carried out at 0.1 MPa and 100° C. for 10 hours, and a coupling agent-flame retardant was obtained after post-treatment; wherein the molar ratio of the flame retardant to the silane coupling agent A was 1:2;

[0291] (3) Preparation of coupling agent-anti-drip agent;

[0292] After adding silane coupling agent B and catalyst to the anti-drip agent solution, reacting at 0.3 MPa and 120° C. for 8 hours, and post-treating to obtain coupling agent-anti-drip agent; wherein the molar ratio of the anti-drip agent to the silane coupling agent B is 1:2, and the mass of the catalyst is 0.2% of the mass of the anti-drip agent;

[0293] (4) Preparation of anti-drip type organic-inorganic flame retardant;

[0294] (4.1) adding the stripping agent solution to the layered α-zirconium phosphate dispersion at a rate of 1 second / drop, accompanied by mechanical stirring and ultrasound during the addition, and continuing to react until the pH value is 7 after the addition is completed; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.6;

[0295] (4.2) Adjust the pH value of the reaction system to 3 with an acid solution, centrifuge (speed 6000r / min), remove the upper liquid, and obtain a translucent paste-like liquid;

[0296] (4.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 15 wt%;

[0297] (4.4) After mixing a coupling agent-flame retardant, a coupling agent-anti-melting agent, and a paste in a mass ratio of 1:1:3 to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system; wherein the mass of the mixed solvent of ketone and alcohol is 2.9 times the mass of the mixture;

[0298] (4.5) The mixed reaction system was placed in an ice-water bath and stirred for 40 min, and then NaOH solution was added dropwise at a rate of 4 s / drop. After the addition was completed, the temperature was raised to 60°C and the mixture was reacted for 20 h. After post-treatment, an anti-melting organic-inorganic flame retardant was obtained; wherein the mass of the NaOH solution was 0.11 times the mass of the mixed solvent of ketone and alcohol.

[0299] The particle size of the final anti-drip organic-inorganic flame retardant is 2-3 μm, the branching degree is 38%, the initial thermal decomposition temperature is 375°C, and an exothermic peak appears at 418°C on the DSC test curve.

[0300] An application of an anti-drip organic-inorganic flame retardant, the anti-drip organic-inorganic flame retardant prepared in this embodiment is melt-blended with polyester chips (manufacturer is China Petrochemical Corporation, brand FG720) and then injection molded to form a flame-retardant anti-drip plastic product; wherein the process parameters of melt blending are: screw zone 1 temperature 240°C, zone 2 temperature 260°C, zone 3 temperature 270°C, zone 4 temperature 275°C, zone 5 temperature 270°C, zone 6 temperature 260°C, zone 7 temperature 260°C; injection molding process parameters are: nozzle temperature 260°C, stage 1 temperature 265°C, stage 2 temperature 270°C, stage 3 temperature 265°C.

[0301] The content of anti-drip type organic-inorganic flame retardant in the final flame retardant and anti-drip plastic product is 3.5wt%; the complex viscosity of the flame retardant and anti-drip plastic product at 370°C is 235Pa·s, the melt index at 275°C and 2.16kg is 129g / 10min, the LOI is 34%, and the UL-94 reaches V0 grade.

Claims

1. A method for preparing an anti-drip type organic-inorganic flame retardant, characterized in that: A system containing a monolayer of α-zirconium phosphate, a coupling agent-flame retardant, and a coupling agent-anti-drip agent is subjected to a co-hydrolysis reaction to obtain an anti-drip type organic-inorganic flame retardant; The coupling agent-flame retardant is obtained by reacting the active functional group of the flame retardant with the active functional group of the silane coupling agent A; The coupling agent-anti-drip agent is obtained by reacting the active functional group of the anti-drip agent with the active functional group of the silane coupling agent B; the structural formula of the anti-drip agent is as follows: In the formula, -R- is -CH=CH-, -C≡C-, -CH=N- or -N=N-; at least one of -R1 to -R6 is an active functional group, which is -NH2, -COOH or -SO3H, and the rest are -H; During the co-hydrolysis reaction, the hydrolyzable functional group of silane coupling agent A becomes -OH connected to the silicon atom, and the hydrolyzable functional group of silane coupling agent B becomes -OH connected to the silicon atom. Different -OH connected to the silicon atom react with each other, and -OH connected to the silicon atom reacts with P-OH on the monolithic α-zirconium phosphate. The flame retardant is DOPO, and the silane coupling agent A is γ-methacryloxypropyltrimethoxysilane or vinyltrimethoxysilane; Silane coupling agent B is γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane or N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane; The branching degree of the anti-drip type organic-inorganic flame retardant is 30-40%.

2. The method for preparing an anti-drip type organic-inorganic flame retardant according to claim 1, characterized in that: The preparation process of the coupling agent-flame retardant is as follows: after dropping silane coupling agent A into the flame retardant solution, adjusting the pH value of the system to 7-8, reacting at 0.1 MPa and 25-120° C. for 3-12 hours, and post-treating to obtain the coupling agent-flame retardant; The concentration of the flame retardant solution is 10-20 wt%, and the solvent is methanol, ethanol, toluene, dichloromethane, chloroform, acetone, dimethyl sulfoxide or DMF; The molar ratio of the flame retardant to the silane coupling agent A is 1:1-3.

3. The method for preparing an anti-drip type organic-inorganic flame retardant according to claim 1, characterized in that: The preparation process of the coupling agent-anti-melting drip agent is as follows: after adding silane coupling agent B and catalyst to the anti-melting drip agent solution, reacting at 0.1-0.3MPa and 25-120°C for 3-12h, and post-treating to obtain the coupling agent-anti-melting drip agent; The concentration of the anti-drip agent solution is 10-20 wt %, and the solvent is toluene, dichloromethane, chloroform, acetone, dimethyl sulfoxide or DMF; The molar ratio of the anti-drip agent to the silane coupling agent B is 1:1-2; The catalyst is azobisisobutyronitrile, 1,3-dicyclohexylcarbodiimide or p-toluenesulfonic acid; The mass of the catalyst is 0.05 to 0.2% of the mass of the anti-dripping agent.

4. The method for preparing an anti-drip type organic-inorganic flame retardant according to claim 1, characterized in that: The specific steps are as follows: (1) using a stripping agent to strip the layered α-zirconium phosphate in a solvent to obtain a paste consisting of a single layer of α-zirconium phosphate and a solvent; The water content of the paste is 10-15wt%; (2) after mixing the coupling agent-flame retardant, the coupling agent-anti-dripping agent, and the paste to obtain a mixture, a mixed solvent of ketone and alcohol is added thereto to obtain a mixed reaction system; The mass ratio of coupling agent-flame retardant, coupling agent-anti-drip agent, and paste is 1:1:2.5-3; In the mixed solvent of ketone and alcohol, the volume ratio of ketone to alcohol is 4 to 7:1, the ketone is acetone or methyl ethyl ketone, and the alcohol is methanol or ethanol; The mass of the mixed solvent of ketone and alcohol is 2.8 to 3.2 times the mass of the mixture; (3) placing the mixed reaction system in an ice water bath and stirring for 30 to 60 minutes, then dropping a NaOH solution thereinto, heating the system to 60 to 70° C. after the addition is complete, and reacting the system for 20 to 24 hours. After post-treatment, an anti-melting droplet type organic-inorganic flame retardant is obtained; The concentration of NaOH solution is 0.1-1 mol / L, and the solvent is water; The mass of the NaOH solution is 0.1 to 0.12 times the mass of the mixed solvent of the ketone and the alcohol; The drop acceleration rate is 3-4s / drop.

5. The method for preparing an anti-drip type organic-inorganic flame retardant according to claim 4, characterized in that: Step (1) is as follows: (1.1) adding the stripping agent solution dropwise to the layered α-zirconium phosphate dispersion at a dropping speed of 1 to 2 seconds per drop, accompanied by mechanical stirring and ultrasound, and continuing the reaction after the dropping is completed until the pH value is 7 to 8; The stripping agent is one or more of D-aminopropanol, 4-amino-1-butanol, 2-aminocyclohexanol, 6-amino-1-hexanol, 3-aminobutanol, 3-amino-1,2-propylene glycol, tromethamine, tetrabutylammonium hydroxide, and hexadecyltrimethylammonium hydroxide; The concentration of the stripping agent solution is 10wt%, and the solvent is deionized water; The average particle size of the layered α-zirconium phosphate is 2 μm; The concentration of the layered α-zirconium phosphate dispersion is 10-15 wt %, and the solvent is deionized water; The mass ratio of layered α-zirconium phosphate to stripping agent is 1:0.6-0.8; (1.2) adjusting the pH value of the reaction system to 2-3 with an acid solution, centrifuging, removing the upper liquid, and obtaining a translucent paste-like liquid; The acid solution is a hydrochloric acid aqueous solution, a nitric acid aqueous solution or a phosphoric acid aqueous solution; (1.3) After adding deionized water to the translucent paste-like liquid, stir, centrifuge, remove the upper liquid, repeat the above operation 3 times, and then perform rotary evaporation to obtain a paste.

6. The anti-melting droplet type organic-inorganic flame retardant prepared by the preparation method of an anti-melting droplet type organic-inorganic flame retardant as claimed in claim 4 or 5, characterized in that: The particle size of the anti-drip organic-inorganic flame retardant is 2 to 3 μm, the initial thermal decomposition temperature is >350°C, and an exothermic peak appears between 380°C and 420°C on the DSC test curve.

7. The use of the anti-drip type organic-inorganic flame retardant according to claim 6, characterized in that: The anti-melting dripping type organic-inorganic flame retardant and polymer chips are melt-blended and then injection-molded to obtain a flame-retardant anti-melting dripping plastic product.

8. The use according to claim 7, characterized in that: The content of the anti-melting dripping type organic-inorganic flame retardant in the flame-retardant anti-melting dripping plastic product is 3-5wt%; The polymer slice is a polyester slice, and the flame retardant and anti-drip plastic product has a melt index of 120-150 g / 10 min at 275° C. and 2.16 kg, a LOI of 33-35%, a UL-94 V0 grade, and a complex viscosity of 208-273 Pa·s at 370° C.

Citation Information

Patent Citations

  • Washable flame-retardant anti-dripping polyester cotton 65 / 35 fabric and preparation method thereof

    CN116427173A

  • Modified POSS (Polyhedral Oligomeric Silsesquioxane) flame retardant as well as preparation method and application thereof in regenerated polyester

    CN116693859A

  • High-temperature-resistant flame-retardant polyester fiber and preparation process thereof

    CN116770453A

  • Cage molecule-containing flame retardant, preparation method thereof and application of cage molecule-containing flame retardant in regenerated products

    CN116813909A

  • High-strength flame-retardant anti-dripping polyester fiber and preparation method thereof

    CN117512802A